Investigations of hexagonal boron nitride: bulk crystals and atomically-thin two dimensional layers - Sperber, Jared L. (Kansas State University, 2016)
Hexagonal boron nitride has been used as an inert, refractory material with excellent resistance to thermal decomposition and oxidation for more than fifty years. In the past few years, hBN has been targeted for potential electrical and optical devices such as neutron detectors, ultraviolet light emitters, deep ultraviolet light detectors, and substrates for graphene and other atomically-thin two-dimensional materials. All of these potential applications benefit from high quality, single crystals, with thicknesses varying from nanometers to microns. This research was undertaken to investigate four aspects of hBN crystal growth and recovery. (1) In an effort to optimize hBN crystal growth from a nickel-chromium flux, a series of stepped cooling experiments were undertaken. The temperature profile was stepped in a way as to promote growth in both the a and c directions, at their optimal growth conditions. Crystals were found to be typically 100-500 µm across and thickness of approximately 20-30 µm with a pyramid-like crystal habit. (2) A method for the removal of hBN crystals prior to freezing of the metal flux was demonstrated using a specialized hot pressed boron nitride crucible capable of removing hBN crystals from the flux in situ. (3) Growth of isotopically pure hBN crystals was undertaken. By modifying the crucible material for solution growth, enrichment of hBN crystals over 90% was accomplished. (4) Exfoliation of hBN has many potential applications, specifically as graphene-hBN heterostructures where layers approaching thicknesses of single atoms are most effective surface to interact with graphene as an electronic device. Several methods were tested toward exfoliating a single crystal resulting in few-layered hexagonal boron nitride nanosheets. As a result of these investigations a greater understanding of hBN bulk growth, its isotopic enrichment, its recovery, and its exfoliation was obtained.
Keywords: Hexagonal boron nitride; Bulk crystal growth; Exfoliation; Boron-10 neutron detector